Artificial polyploidy as a tool for improving growth and stress resilience in tree species - Bharati, Rohit; Severová, Lucie (Frontiers in Forests and Global Change, 2025)
Woody trees are invaluable to ecosystems and economies, providing essential resources such as timber, fuel, food, and medicine. Trees also play a critical role in carbon sequestration, biodiversity conservation, and soil stabilization, making their health and productivity vital in the face of global environmental challenges. However, the changing climate and escalating threats from pests, diseases, and abiotic stresses pose significant risks to woody tree species, necessitating the development of sustainable approaches to enhance their growth and resilience. One promising strategy is artificial polyploidization, a biotechnological method that induces multiple complete sets of chromosomes, which has been successfully used in agriculture and horticulture to improve plant traits like growth and stress resistance. Despite its proven benefits in herbaceous and crop plants, polyploid induction remains underutilized in woody trees. It holds potential for enhancing both the ecological roles of woody trees, as well as their economically valuable characteristics. This mini-review explores the potential of polyploidy as a sustainable tool to boost growth and stress resilience in woody species. The mini-review examines the potential challenges associated with polyploid induction in woody trees, including technical difficulties and knowledge gaps, while also providing future directions for research and application.